Ecological risk assessment of oilfield soil through the use of machine learning combining with spatial interaction effects - Shihan Wang; Mingxia Zheng; Yushan Tian; Hongyu Ding; Lina Yan; Beidou Xi; Yuanyuan Sun; Jing Su (Ecotoxicology and Environmental Safety)
With the intensification of oil extraction activities, total petroleum hydrocarbons (TPHs) and toxic elements contamination in soil around oil wells have become severe environmental problems. This paper proposed a novel method based on machine learning (ML) and remote sensing (RS) to predict concentrations of TPHs and toxic elements in the soil around 1252 oil wells for pollution investigation and monitoring in the Huabei Oilfield in China. RS can obtain variables that are closely related to soil pollution, such as the fractional vegetation cover (FVC), soil type and topographic factors. which can help reveal the pollution driving mechanism combining with ML. ML was used to predict pollutant concentrations, with predictors such as the distribution of oilfield capacity facilities interpreted by RS imagery. Combining RS and ML helps uncover pollution driving mechanisms. The potential ecological risk index (RI) method was utilized to assess ecological risks, and spatial autocorrelation analysis was conducted to determine the spatial distribution characteristics of the pollutants. The results indicated that the Gradient Boosting Machine (GBM) model exhibited strong performance in predicting concentrations of TPHs (R2=0.7730), As (R2=0.8614), Pb (R2=0.8678), Ni (R2=0.7539), Cd (R2=0.7447), and Hg (R2=0.6270) in soil. Oil extraction activities, land use, and soil properties are the dominant factors influencing the accumulation of TPHs and toxic elements. The ecological risk assessment combined with bivariate LISA mapping identified priority areas for risk control, of which 22.73 % were with no risk, 18.18 % were with combined TPHs and toxic elements risk, 8.67 % were with toxic elements risk, 6.61 % were with TPHs risk, and 26.04 % were with uncertain risk. The results can be applied to provide technical support for soil risk management and industrial site planning in the oilfield and surrounding area.